Tectonics vs. erosion: evidences from apatite fission track and Rb-Sr (Biotite and Muscovite) thermochronology, Arunachal Himalaya - Pebam, James; Jain, AL; Kumar, R; Singh, Sandeep; Lal, Nand (Himalayan Journal of Sciences, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> DOI = 10.3126/hjs.v5i7.1295 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.103-105